Evolution of Eye Reduction and Loss in Trilobites and Some Related Fossil Arthropods - Brigitte Schoenemann (Emerging Science Journal, 2018)
The fossil record of arthropod compound eyes reflects different modes and occasions of eye reduction and blindness. In the best-studied fossil examples, the trilobites [trilobites: extinct arthropods, dominant during the Palaeozoic], which have an excellent geological record, eyes are primary structures, and in all known genera which lack them, eye-loss is always secondary. Once the eyes were lost, they never were never re-established. The most striking examples occur in the Upper Devonian, when two unrelated major groups of trilobites, with different kinds of eyes, underwent eye reduction and even total loss of the eyes over the same time period, undoubtedly due to long-term environmental change. One reason is that a mud blanket spread over a vast area, there was no firm substrate, and many trilobites became small and many became endobenthic, reducing or losing their eyes in the process. Toxic environmental conditions may also have had an effect. Certain coeval forms remained, however, which still possess perfectly good compound eyes. Either they found vacant refuges where they could survive, or alternatively their visual systems were elaborate enough to adapt to the changing conditions. Another inducement for evolving small, reduced compound eyes is to become a tiny organism oneself, with simply not enough space to establish a regular and functional compound eye, and in such minaturised eyes special adaptations for capturing enough photons are necessary. Thus very small compound eyes often establish wide acceptance angles of their ommatidia, collecting light over large angular ranges of space and it is beneficial to have a wide rhabdom provided that it is short, has a wide lens diameter, and perhaps even possess highly sensitive receptor cells. We find such a miniaturised system in the first recorded planktonic trilobite. Another kind of reduction of a compound eye, or parts of it, also occurs, if selective pressure claims for a high specialisation of eyes that results in several facets fusing into a single functional unit. This probably can be found in phacopid trilobites, ~400 million years old. Here the enlarged aperture of a resulting large lens may allow vision under dim light conditions such as at greater depth. The fossil record gives relatively little evidence about parasites, which often have reduced eyes. Agnostida are blind relatives of trilobites which lived during the Cambrian and Ordovician. An early suggestion was that some of these were parasitic, but this was never commonly adopted. Finally penstastomids (Crustacea), worm-like parasitic organisms, already have been blind from the Cambrian (~487Ma).